Plasmonically-enhanced reconfigurable photodetector based on graphene/Sb2S3 heterojunction - Xiaojuan Lian; Shiyu Li; Jiyuan Jiang; Wen Huang; Nan He; Xiaoyan Liu; Jie Wu; Zhou Wang; Gangyi Zhu; Lei Wang (Applied Physics Express)
Graphene photodetectors face challenges like weak absorption and narrow spectral range. To overcome these weakness, we proposed a novel photodetector based on a Gold (Au)/Graphene/Chalcogenide (Sb _2 S _3 ) hetero-junction, leveraging surface plasmonic and phase-transition effects. Simulations show that optimizing Au and Sb _2 S _3 nanoantenna thicknesses and diameters can achieve an absorption efficiency of 0.9 for both amorphous and crystalline states, with an adjustable wavelength range of 200 nm. The device demonstrates superior performance, including a responsivity of 125 A W ^−1 , quantum efficiency of 1.36 × 10 ^4 %, and detectivity of 2.25 × 10 ^9 Jones, offering a pathway to next-generation optoelectronic chips.